Transformasi Keterampilan Guru Mengembangkan Perangkat Ajar Berbasis Deep Learning Berbantuan AI : Program Pelatihan di Banjarmasin Utara - Bagus Aulia Iskandar; Ahmad Riandy Agusta; M. Ziyan Takhqiqi Arsyad; Arif Rahman Prasetyo; Dede Dewantara; Yayuk Hartini; Elma Mufida; Nur Saniah Widya (LPPM Universitas Harapan Bangsa Purwokerto, 2026)
Elementary education is currently facing the challenges of the Industrial Revolution 4.0 and Society 5.0, necessitating effective curriculum innovation to equip students with future competencies. The Deep Learning (DL) approach is a national priority, but shifts in learning activity policies determine teachers' readiness to implement it. Low understanding and minimal curriculum innovation, especially in the context of Deep learning integration management, pose significant obstacles to effective learning implementation. The Elementary School Teacher Working Group (KKG) in North Banjarmasin District, as the partner, directly experiences these constraints, reinforcing the urgency of this intervention.The objective of this Community Service program is to enhance the capacity of elementary school teachers in designing Deep Learning-integrated curricula. The method employed is intensive training based on local and applied case studies, specifically designed to directly improve teachers' managerial and innovative skills. The anticipated impact is an increase in teacher awareness and competence in managing curricula that are adaptive and relevant to the digital era. This program not only empowers local teachers but also aligns with the Merdeka Belajar Kampus Merdeka (MBKM) policy and the University's Key Performance Indicators (IKU 2, 7, 8, and 9) through strategic collaboration and project-based learning. Thus, this training serves as a strategic step to bridge the competency gap and support national education innovation.